2017
DOI: 10.1037/neu0000295
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of closing-in.

Abstract: When performing complex actions, like graphic copying or imitation of gestures, some patients may perform these actions very close to, or directly on the top of the model. This peculiar behavior, known as closing-in, is the focus of the present literature review, which will provide a critical picture of the research in this field, highlighting the difficulties in defining and assessing closing-in and the contrasting results about the nature and the characteristics of this phenomenon. Most importantly, we will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(49 citation statements)
references
References 72 publications
(259 reference statements)
8
24
0
17
Order By: Relevance
“…The enhanced tendency to deviate towards task-relevant distractors observed in CIB+ compared to the other groups emerged despite controlling for the severity of the cognitive decline. As previous work has shown that cognitive decline plays a crucial role in CIB (Ambron et al, 2009b;Ambron & Della Sala, 2017), the fact that an association between CIB and motor distractibility emerges despite controlling for severity reinforces our conclusions.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The enhanced tendency to deviate towards task-relevant distractors observed in CIB+ compared to the other groups emerged despite controlling for the severity of the cognitive decline. As previous work has shown that cognitive decline plays a crucial role in CIB (Ambron et al, 2009b;Ambron & Della Sala, 2017), the fact that an association between CIB and motor distractibility emerges despite controlling for severity reinforces our conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…Following this account, individuals with CIB would show a larger tendency to deviate towards the distractor than individuals without CIB or HC. These predictions where met as movement trajectories of CIB+ individuals were more prone to veered towards the distractor location than the other groups, in particular when the distractor was task-relevant, consistent with the interpretation of CIB as a magnetic attraction of the movement trajectories towards the focus of attention (Ambron & Della Sala, 2017). Of course, in the standard copying tasks in which CIB is traditionally observed, the CIB sign is towards a task-relevant focus of attention, the model.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations